Design of a Part of a Production Line for Sorting Products Packed in Metal Cans - خنيسي, محمد (Latakia University Journal -Engineering Sciences Series, 2025)
Sorting metal products in industrial production lines is a vital step that contributes to improving efficiency and quality. Sorting helps identify defective or non-conforming products, which reduces the percentage of defects in the final production and ensures that the materials used in manufacturing meet the required standards, enhancing the final product's quality. Sorting metal products increases the efficiency of the sorting process as sorting products helps reduce the waste of raw materials, which leads to better use of resources, reduces costs, and facilitates the recycling process of metals, which contributes to preserving the environment and reducing waste. Sorting metal products helps speed up sorting processes as the sorting process allows products packed in metal cans to be quickly identified, which speeds up the delivery process, increases customer satisfaction, facilitates inventory organization, and helps manage the supply chain more effectively. In this research, a part of a production line was designed and implemented that inspects the products passing through; it automatically sorts the products packed in metal cans and removes them from the production process while allowing the rest of the products to continue in the production process. This is done by using position sensors to determine the location of the product in the production line in addition to an inductive sensor to check the element and actuators such as a stepper motor to move the production line and an audible alarm to identify defective parts if they are on the production line. The project was implemented practically, and the accuracy and validity of all theoretical steps were confirmed by testing a group of products packed in several types of cans. Only the products packed in metal cans were sorted and removed from the production line, while the rest continued in the production process.